Numerical investigation of scour behavior around complex piers under flood conditions - Qin, Qiang; Shi, Liangliang; Li, Yufei; Li, Yujie; Qin, Haozhou; Ren, Gang; Yang, Zhiying (Frontiers in Built Environment, 2025)
IntroductionLocal scour at bridge piers is a primary cause resulting bridge failure, a risk that is significantly exacerbated under extreme hydrodynamic events such as floods.MethodsThis study presents a numerical investigation of the scour behavior around a complex bridge pier, consisting of a pier, pile cap, and pile group, focusing on the effect of pile cap embedment depth on the flow field and scour characteristics. A three-dimensional numerical model was developed based on a railway bridge, simulating scour processes under flow velocities of 4.0 m/s and 6.0 m/s.Results and discussionThe results reveals that the relative embedment depth of the pile cap significantly influences the scour characteristics. When the pile cap is above the riverbed, the scour area predominantly develops in the longitudinal direction (along the flow), forming an inverted cone shape. Conversely, when the pile cap is embedded in the riverbed, both the scour extent and depth decrease significantly, with the scour predominantly concentrated on either side of the pile cap in a round end distribution. Furthermore, the maximum scour depth follows a nonlinear trend, initially increasing and then decreasing as the pile cap’s elevation decreases. The maximum scour depth occurs when the pile cap is flush with the riverbed, while a significant reduction in scour depth is observed when the cap is fully embedded. The findings of this study provide practical guidance for the anti-scour design of bridge complex piers.